The Implementation of School Literacy Program and The Condition of Vocational School Students’ Reading Interest - Permatasari, Hana Riana; Permana, Johar; Rohmah, Siti Khozanatu (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
One of important skill in 21st century education is literacy skill, specially in vocational school students that should be ready to enter the job world. The problem that is happening now is Indonesian students’ literacy skill is still low, so is the reading interest. The objectives of this study are to explore the implementation of school literacy program, to analyze the students’ reading interest, to identify the problems in school literacy program, and to arrange the improvement of school literacy program. This study conducted in two vocational schools in Bandung City. The method used is qualitative method with technique observation, interview, and questionnaire distribution. The results of this study are all two schools have implemented school literacy program well, the condition of students’ reading interest at three school is in good condition, the problems in school literacy programs is about time management and teachers’ quality, and it can be implemented community based school literacy program to develop the program. The conclusion is the government together with schools need to develop the community based school literacy program to improve the quality of program and increase the students’ reading interest